2011
DOI: 10.1309/ajcpfkolgl6pmof3
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Immunohistochemical and Histochemical Studies in the Classification of Lung Adenocarcinoma and Squamous Cell Carcinoma in Cytologic Specimens

Abstract: Histologic subtyping of non-small cell lung carcinoma (NSCLC) is important because the efficacy of new treatments depends on tumor histologic features. We assessed the diagnostic accuracy of classification of lung adenocarcinoma and squamous cell carcinoma (SCC) on cytologic and biopsy specimens based on cytomorphologic studies alone or in combination with ancillary studies compared with resection specimens. Compared with adenocarcinoma, the diagnosis of SCC was based more often on cytomorphologic studies alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 36 publications
5
53
1
1
Order By: Relevance
“…In the present study, the mucin production was mostly evidenced in adenocarcinomas as compared with the rest of lung tumors, similar to previous reports [22,27,28]. Interestingly, the presence of mucin was signifi cantly higher in NSCLC samples displaying increased degree of cytological atypia.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the mucin production was mostly evidenced in adenocarcinomas as compared with the rest of lung tumors, similar to previous reports [22,27,28]. Interestingly, the presence of mucin was signifi cantly higher in NSCLC samples displaying increased degree of cytological atypia.…”
Section: Discussionsupporting
confidence: 92%
“…Both HMWK and P63 are useful to differentiate SCC from adenocarcinoma and poorly differentiated SCC from SCLC and large cell neuroendocrine carcinoma. [9] In our study, out of 20 cases reported as SCC and 4 cases as NSCLC in H&E, HMWCK was expressed in 20 cases (sensitivity 83.3%) ( fig.1) and P63 showed immunopositivity in 22 cases (sensitivity 91.7%) ( fig.2). P63 was not expressed in any of the adenocarcinoma cases with 100% specificity.…”
Section: Discussionsupporting
confidence: 46%
“…[10] In a study by R.Ocque, N.Tochigi et al, 2011, P63 expression was found in all the 30 cases of SCCs with 100% sensitivity. [9] Recent studies have proposed a panel of markers for pulmonary adenocarcinomas-CK-7, CK-20, TTF-1. Primary lung adenocarcinoma shows strong and diffuse positivity with CK-7.…”
Section: Discussionmentioning
confidence: 99%
“…VATS is often required toget a sample of the size that is suitable for definite diagnosis [7]. Histomorphological, histochemical and immunohistochemical findings should be evaluated together for the definitive diagnosis of pseudomesotelomatic adenocarcinoma.The specificity of TTF-1, CEA and CD15 as the most useful markers in patients with adenocarcinoma is respectively 100%, 97-98.8%, 93% and 67%.…”
Section: Discussionmentioning
confidence: 99%